Genome-Wide Association Studies Reveal that Diverse Heading Date Genes Respond to Short and Long Day Lengths between Indica and Japonica Rice - Han, Zhongmin; Zhang, Bo; Zhao, Hu; Ayaad, Mohammed; Xing, Yongzhong (Frontiers in Plant Science, 2016)
Rice is a short-day plant. Short-day length promotes heading, and long-day length suppresses heading. Many studies have evaluated rice heading in field conditions in which some individuals in the population were exposed to various day lengths, including short and long days, prior to a growth phase transition. In this study, we investigated heading date under natural short-day conditions (SD) and long-day conditions (LD) for hundreds of accessions and separately conducted genome-wide association studies within indica and japonica subpopulations. Under LD, three and four quantitative trait loci (QTLs) were identified in indica and japonica subpopulations, respectively, two of which were less than 80 kb from the known genes Hd17 and Ghd7. But no common QTLs were detected in both subpopulations. Under SD, six QTLs were detected in indica, three of which were less than 80 kb from the known heading date genes Ghd7, Ehd1 and RCN1. But no QTLs were detected in japonica subpopulation. qHd3 under SD and qHd4 under LD were two novel major QTLs, which deserve isolation in the future. Eleven known heading date genes were used to test the power of association mapping at the haplotype level. Hd17, Ghd7, Ehd1 and RCN1 were again detected at more significant level and three additional genes, Hd3a, OsMADS56 and Ghd7.1, were detected. However, of the detected seven genes, only one gene, Hd17, was commonly detected in both subpopulations and two genes, Ghd7 and Ghd7.1, were commonly detected in indica subpopulation under both conditions. Moreover, haplotype analysis identified favorable haplotypes of Ghd7 and OsMADS56 for breeding design. In conclusion, diverse heading date genes/QTLs between indica and japonica subpopulations responded to SD and LD, and haplotype-level association mapping was more powerful than SNP-level association in rice.